Reactivity of organogold compounds with B(C6F5)3: gold-boron transmetalation via [sigma]-B/[pi]-Au species - Hansmann, Max M.; Rominger, Frank; Boone, Michael P.; Stephan, Douglas W.; Hashmi, A. Stephen K. (Organometallics, 2014)
The reactions of gold-acetylides with B(C6F5)3 afford alkynyl borate species and cationic π-coordinated gold complexes. The analogous reactions with aryl gold species generate gem-diaurated compounds containing a borate counteranion. These new σ-B/π-Au alkynyl borate complexes can be employed as active catalysts in homogeneous catalysis and represent a new silver-free activation pathway. The new alkynyl borate species are fully characterized, and the alkyne fragments are shown to be bound in a σ-B/π-Au fashion. Upon prolonged heating, these compounds undergo a slow C6F5 group transfer to gold affording LAuC6F5 species.
Die Ziffern im Titel sind tiefgestellt, sigma und pi sind als griechische Buchstaben dargestellt
Gesehen am 03.09.2020